Pendampingan Persiapan Pembukaan Sekolah Tatap Muka Terbatas untuk Pencegahan Penularan Covid-19 di SDN 09 Simpang Tigo, Kecamatan Sungai Pua, Kabupaten Agam - Putri Nilam Sari; Azyyati Ridha Alfian; Fea Firdani; Anisa Rahmatul Uswat; Puti Oneyna Raisa (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
Almost all communities around SDN 09 Simpang Tigo choose to do classroom learning for elementary school children. In fact, until April 7, 2021, Agam Regency was still in the orange zone (moderate risk) because there were still many new cases of COVID-19 in this area. From initial observations, many school residents have not implemented good and correct health protocols and increase the risk of spreading COVID-19. The purpose of this activity was to assess the readiness of schools to carry out limited classroom learning, increase school commitment in implementing health protocols, increase student knowledge about COVID-19, maintain a healthy environment, and train themselves to wash hands with soap and running water. The activity was carried out using the lecture method using media posters. Schools were provided with a handwashing system with a tread system. The activity results showed that schools had begun to implement health protocols but had not been maximized. After counseling, there was an increase in students' knowledge from 45.9% to 85.9%. Students had also been able to practice handwashing with soap properly. Students who were given counseling are expected to become motor drivers to reduce the transmission of COVID-19 in schools and living areas.